A Patient with Advanced Gastric Cancer Presenting with Extremely Large Uterine Fibroid Tumor - Kwang-Kuk Park; Song-I Yang (Case Reports in Surgery)
Introduction. Uterine fibroid tumors (uterine leiomyomas) are the most common benign uterine tumors. The incidence of uterine fibroid tumors increases in older women and may occur in more than 30% of women aged 40 to 60. Many uterine fibroid tumors are asymptomatic and are diagnosed incidentally. Case Presentation. A 44-year-old woman was admitted to our hospital with general weakness, dyspepsia, abdominal distension, and a palpable abdominal mass. An abdominal computed tomography scan showed a huge tumor mass in the abdomen which was compressing the intestine and urinary bladder. Gastroduodenal endoscopic and biopsy results showed a Borrmann type IV gastric adenocarcinoma. The patient was diagnosed with gastric cancer with disseminated peritoneal carcinomatosis. She underwent a hysterectomy with both salphingo-oophorectomy and bypass gastrojejunostomy. Simultaneous uterine fibroid tumor with other malignancies is generally observed without resection. But in this case, a surgical resection was required to resolve an intestinal obstruction and to exclude the possibility of a metastatic tumor. Conclusion. When a large pelvic or ovarian mass is detected in gastrointestinal malignancy patients, physicians try to exclude the presence of a Krukenberg tumor. If the tumors cause certain symptoms, surgical resection is recommended to resolve symptoms and to exclude a metastatic tumor.